Control, temporal orientation, and the cross-linguistic grammar of trying. Issue 1 (25th October 2017) - Grano, Thomas
Abstract : The verb try plays a starring role in many example sentences in the control literature. But one of its most basic properties has eluded satisfying explanation: for many speakers of English, try rejects non-control infinitival complements, as in % I tried for John to notice me or % John tried for there to be food on the table . A number of scholars have hypothesized that this fact about try has a semantic basis, but this hypothesis has yet to be fully reconciled with the problem of cross-dialectal and cross-linguistic variation and with existing formal semantic approaches to try -sentences. In this paper, based in part on a novel observation from Spanish and Hebrew about how try 's complement type interacts with its temporal orientation, I aim to further substantiate the semantic approach to try 's behavior. The proposal is couched in an explicit compositional treatment of the formal semantics of try -sentences, whereby non-control try -sentences induce a presupposition failure which can be repaired in some languages via a coercion mechanism that is independently detectable in that in some languages it enables a future orientation for the complement. The implication is that cross-linguistic variation in the inventory of coercion mechanisms obscures an underlyingly principled semantic basis for try 's behavior.